Microbial lipid-based biodiesel production using wastewater: opportunities and challenges - Ameera Al Shehhi; Yasmine Souissi; Anu Sadasivan Nair; Zeba Usmani; Minaxi Sharma; Nallusamy Sivakumar (Bioresources and Bioprocessing)
Abstract Rising environmental concerns and fossil fuel depletion necessitate the search for sustainable, alternative energy sources. Biodiesel is emerging as a viable alternative owing to its biodegradability, low toxicity, and reduced greenhouse gas emissions. This review highlights the environmental and economic advantages of biodiesel, with a special emphasis on microbial lipids from wastewater as a promising third-generation feedstock. The novelty of this review is the comprehensive evaluation of wastewater and sewage sludge as low-cost, nutrient-rich substrates for microbial lipid production. In this review, the biodiesel production by direct lipid extraction and microbial conversion routes is discussed. Biodiesel production from different types of industrial wastewaters, such as municipal, dairy, pulp and paper, brewery, and textile wastewater using oleaginous microorganisms is discussed as well. This review revealed that lipid content in different microbes ranged from 27 to 90% when different wastewaters were used as substrates. Further, this review compares the fuel properties of biodiesel derived from plant oils, animal fats, and microbial lipids, their fatty acid profiles, and estimated production costs, and it varies from 0.1 to 0.83 USD/L. In addition, this review also focuses on the biodiesel production from wastewater using microalgae, fungi, and bacteria. Biodiesel with a high cetane number of 64.47 was produced by Cryptococcus curvatus. Finally, key challenges in producing biodiesel from wastewater and future prospects are discussed, emphasizing the potential of wastewater as a substrate for sustainable biodiesel production. Graphical abstract